2012
DOI: 10.1542/peds.2011-0583
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinoviruses in Severe Respiratory Disease in Very Low Birth Weight Infants

Abstract: HRV is an important and frequent pathogen associated with severe respiratory infections in VLBW infants. Bronchopulmonary dysplasia and the absence of breastfeeding are risk factors for hospitalization. The results of our study reveal that HRV is the predominant pathogen of respiratory infections in premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 43 publications
6
81
0
Order By: Relevance
“…28 Thus, the premature child may be at higher risk of developing a more severe respiratory disease regardless of whether the virus causing the infection is HRV or RSV. 29 This possibility was supported by our study, because we also observed an association between prematurity and disease severity in HRV single infection. Similar to our findings, Watanabe et al 3 showed involvement of congenital heart diseases in severe HRV infection.…”
Section: Discussionsupporting
confidence: 80%
“…28 Thus, the premature child may be at higher risk of developing a more severe respiratory disease regardless of whether the virus causing the infection is HRV or RSV. 29 This possibility was supported by our study, because we also observed an association between prematurity and disease severity in HRV single infection. Similar to our findings, Watanabe et al 3 showed involvement of congenital heart diseases in severe HRV infection.…”
Section: Discussionsupporting
confidence: 80%
“…Although RV infections have long been thought to be limited to the common cold and mild self-limiting upper respiratory illnesses, the application of improved viral molecular detection methods has substantially improved understating of the epidemiology and the clinical significance of RV, particularly among high risk children [9498]. In a 2-year prospective study, RV was detected in 41% of all episodes of acute respiratory illnesses and 33% of related hospitalisations during the first year of life in a cohort of preterm infants [99]. The risk and severity of RV-related respiratory illnesses are considerably elevated among preterm infants with BPD, with a more than 5-fold increased risk of RV-related hospitalisation among infants with BPD compared to non-BPD infants [99].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…In a 2-year prospective study, RV was detected in 41% of all episodes of acute respiratory illnesses and 33% of related hospitalisations during the first year of life in a cohort of preterm infants [99]. The risk and severity of RV-related respiratory illnesses are considerably elevated among preterm infants with BPD, with a more than 5-fold increased risk of RV-related hospitalisation among infants with BPD compared to non-BPD infants [99]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…As a comparison at a regional level, in a prospective cohort study of 207 very low-birth weight (birth weight 1,500 g) pre-mature infants followed until 1 year of age in Buenos Aires, Argentina, the incidence of RSV-associated hospitalizations was approximately 90 per 1,000 child-years of follow-up. 6,7 Children with underlying conditions, such as pre-maturity, chronic lung disease, congenital heart disease, and immunosuppression, are at high risk for severe RSV disease. 8 Prematurity, a major risk factor for RSV hospitalization, goes along with small, immature, and vulnerable airways, an immature immune system, an incomplete transfer of maternal antibodies, and an inadequate cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In Latin America, there are several studies on the epidemiology of RSV infections in children [2][3][4][5] ; however, there are limited data on the disease burden of these infections in high-risk groups, such as pre-term infants. 6,7 Prevention of RSV disease relies on infection control and hygiene measures as well as provision of immunoprophylaxis in select infants. However, the prophylaxis is expensive, and therefore, targeting the recipient population and timing of administration are important for optimal effectiveness and judicious use of limited healthcare resources.…”
Section: Introductionmentioning
confidence: 99%